Robotic surgery: change in new surgery techniques - mitra zandyeh; naemeh fakhar; mina karami (Journal of Holistic Nursing and Midwifery)
Medical science experts have reached scientific and technological improvements in recent ‎decades and have turned surgery into a routine treatment by controlling its complications. ‎Cumulative changes in surgery resulted in decreased pain and discomfort and controlled ‎complications. The developmental path and changes have resulted in endoscopic with minimal ‎invasive surgery (MIS) in which only few small incisions are made on the body and surgery is ‎done through video control which otherwise required more and larger incision with more ‎complication. But this method with all the usefulness has some problems such as discrepancy ‎between surgeon's eye and hand, indirect and two dimensional vision, limited degree of ‎freedom of instruments and surgeon's fatigue. In addition this type of surgery needs complete ‎education and skill. The sum of these factors limits the use of MIS. In order to overcome these ‎problems, robotic surgery method is invented. In this method like MIS, a few small incisions ‎are made and surgeon is able to perform the surgery from a distance by a three dimension ‎vision by controlling the arms of robots which are similar to the movements of human and are ‎placed around the table of surgery. Despite all the benefits of this method, its high cost limits ‎its use. Although it's hopeful that with the improvements of this method and its usefulness, ‎the costs will decrease. ‎